Food ethics the basics - Sandler, Ronald L. (The basics, 2024)
"Food Ethics: The Basics is a concise yet comprehensive introduction to the ethical dimensions of the production and consumption of food. It offers an impartial exploration of the most prominent ethical questions relating to food and agriculture including: Should we eat animals? Are locally produced foods ethically superior to globally sourced foods? Do people in affluent nations have a responsibility to help reduce global hunger? Should we embrace bioengineered foods? What should be the role of government in promoting food safety and public health? This second edition has been revised and updated throughout, not only to take in the latest empirical and policy information, but also to address the impact of major issues such as the COVID-19 pandemic, Russia's invasion of Ukraine, AI and machine learning, and the rapid growth of the "gig economy". Using extensive data and real-world examples, as well as providing suggestions for further reading, Food Ethics: The Basics is an ideal introduction for anyone interested in the ethics of food"--